2017
DOI: 10.1002/ep.12620
|View full text |Cite
|
Sign up to set email alerts
|

Contamination assessment and the risk associated with the accumulation of trace metals in sediments of the Mitidja plain, Algeria

Abstract: This study was carried out to assess the degree of contamination by trace metals in sediments of the main rivers of the eastern Mitidja plain. In order to achieve this objective, the enrichment factor, the geoaccumulation index and the potential ecological risk were calculated. Possible sources of trace metals in sediments were performed using a multivariate statistical analysis. The concentrations of the studied metals decreased in the order of Fe ≫ Zn > Cr > Pb > Ni > Cu> Cd. The results showed that Cd had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Research has demonstrated that industrial emissions are a dominant source of metal contaminations in riverine sediments worldwide (Tian et al, 2020;Lopes et al, 2014). The high CV value for metals, especially for Cd and Cu with high risk factors, strongly implicated anthropogenic activities as the source of metal contamination (Laribi et al, 2017).…”
Section: Metal Concentrations and Potential Ecological Risk (Per) Assessment In Sedimentsmentioning
confidence: 99%
“…Research has demonstrated that industrial emissions are a dominant source of metal contaminations in riverine sediments worldwide (Tian et al, 2020;Lopes et al, 2014). The high CV value for metals, especially for Cd and Cu with high risk factors, strongly implicated anthropogenic activities as the source of metal contamination (Laribi et al, 2017).…”
Section: Metal Concentrations and Potential Ecological Risk (Per) Assessment In Sedimentsmentioning
confidence: 99%
“…The calculations of most of these indices require background values of the elements. In this study, background concentrations used to compute these indices were taken from literature as 7.8, 19, 0.1, 35, 514, 35, 33 and 37.5 mg/kg for As, Pb, Cd, Cu, Mn, Fe, Ni and Cr respectively [1,6,11,[31][32][33][34], and were kept lower than the threshold limits [35].…”
Section: Surface Sediment Contamination Level Of the Lakementioning
confidence: 99%
“…The C d was determined using equation (6) [33], and it shows the aggregated value of CF of all metals and the metalloid under discussion:…”
Section: Degree Of Contamination (C D )mentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural practices used in these soils, such as the use of agrochemical products and wastewater for soil irrigation could also result in contamination (Khouli and Djabri 2011;Lebik and Ait-amar 2013). Previous trace metal studies in the Mitidja plain have referred to a small local scale (Laribi and Saidani 2016) and to sediment (Laribi et al 2017) and no published data are available at a regional scale.…”
Section: Introductionmentioning
confidence: 99%